Biogeography of parasite abundance: latitudinal gradient and distance decay of similarity in the abundance of fleas and mites, parasitic on small mammals in the Palearctic, at three spatial scales. Issue 11 (September 2018) - van der Mescht, Luther; Warburton, Elizabeth M.; Khokhlova, Irina S.; Stanko, Michal; Vinarski, Maxim V.; Korallo-Vinarskaya, Natalia P.; Krasnov, Boris R.
Graphical abstract: Highlights: No relationship was found between latitude and intraspecific flea or mite abundance. Environment had the greatest effect on spatial variation in parasite abundance. Host abundance affected parasite abundance to a lesser extent. These patterns were generally consistent across spatial scales. Abstract: We tested whether biogeographic patterns characteristic for biological communities can also apply to populations and investigated geographic patterns of variation in abundance of ectoparasites (fleas and mites) collected from bodies of their small mammalian hosts (rodents and shrews) in the Palearctic at continental, regional and local scales. We asked whether (i) there is a relationship between latitude and abundance and (ii) similarity in abundance follows a distance decay pattern or it is better explained by variation in extrinsic biotic and abiotic factors. We analysed the effect of latitude on mean intraspecific abundance using general linear models including proportional abundance of its principal host as an additional predictor variable. Then, we examined the relative effect of geographic distance, biotic and abiotic dissimilarities among regions, subregions or localities on the intraspecific dissimilarity in abundance among regions, subregions or localities using Generalized Dissimilarity Modelling. We found no relationship between latitude and intraspecific flea or mite abundance. In both taxa, environmental dissimilarity explained the largest part of the deviance of spatial variation in abundance, whereas the effect of the dissimilarity in the principal host abundance was of secondary importance and the effect of geographic distance was minor. These patterns were generally consistent across the three spatial scales, although environmental variation and dissimilarity in principal host abundance were equally important at the local scale in fleas but not in mites. We conclude that biogeographic patterns related to latitude and geographic distance do not apply to spatial variation of ectoparasite abundance. Instead, the geographic distribution of abundance in arthropod ectoparasites depends on their responses, mainly to the off-host environment and to a lesser extent the abundance of their principal hosts.